PERAN SCHOOL WELL BEING SEBAGAI MEDIATOR PENGARUH RASA SYUKUR TERHADAP MOTIVASI BELAJAR SISWA - Fira Zalsabila; Basti Tetteng; M. Ahkam Alwi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2025)
This study discusses the case of school well-being (SWB) as a mediator of the influence of gratitude on students' learning motivation using a qualitative approach. This study recruited students of State High School students in Polewali Mandar Regency with a total of 380 people. The instruments used in this study are the SWB measuring tool to measure SWB, the gratitude scale to measure gratitude, and the learning motivation scale to measure learning motivation. After the data collection, the analysis was accomplished based on the SEM (Structural Equation Modelling) test to determine the relationship between variables within the context of this research, test the model fit and identify the direct and indirect effects on the model assisted by the Sobel test to see the mediating effect of school well-being variables. Data in this study has demonstrated that gratitude had a positive and significant direct effect on learning motivation with a figure of 24.7%; gratitude has significant positive and direct influence on school well-being (64.1%); School well-being identified has a positive and significant direct influence on learning motivation (17%); and school well-being was identified as a mediator for the influence of gratitude toward learning motivation indirectly with a figure of 10.9%.